Paths to successful development : (Cambridge University Press, 2002)
The influence of the lifespan approach has been an important feature of recent research in developmental psychology, as has a growing interest in the relationship between personality and development. This important new book, edited by two distinguished psychologists and including the work of many of the leading figures in the field, explores the relationship between personality and devleopment and is unique in focussing on successful development, where developmental psychology in the past seems to have focussed almost entirely on problem behaviour and risk of maladaption.